Two new species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Roraima State, northern Brazil - Boldrini, Rafael; Lima, Lucas Ramos Costa; de Oliveira, Ismael Barreto; de Paiva Ottoni Boldrini, Bianca Maira; Salles, Frederico Falcão (Zootaxa, 2022)
Two new species of Simothraulopsis (Ephemeroptera: Leptophlebiidae) are described and illustrated, based on recent collections and specimens deposited in the Zoological Collection of Universidade Federal de Roraima (UFRR), northern Brazil. Simothraulopsis pacaraima sp. nov. differs from others species by the telopenis being spine-like, short (less than the half of total length of penis lobes) and slightly directed laterally, and the penis lobes with a medial knob between them. Simothraulopsis rainori sp. nov. differs from others species by the telopenis being spine-like, mid-sized (less than the half of total length of penis lobes) and ventrally directed with the apex bent outward, and the penis lobes fused in their basal 1/3, with a well-marked sclerotized region; each lobe is laterally swollen and protruding.